Latvian Original Adverts and Translations in the 1920s and 1930s - Ločmele, Gunta (Vertimo studijos, 2022)
Advertisements in the 1920s and 1930s Latvia were published mainly in Latvian, German and Russian. Besides original adverts for local products, there were numerous translations of advertisements, mainly from German. Translations of translations also circulated in the press, blurring the concept of a source text. Advertising, including translated adverts, made an impact on culture, glorifying feminine beauty in many cases but trivialising women by a specific use of language in others. Advertising also influenced the Latvian language itself. Translators added a second layer of German calques to the ones that already existed. However, new terms coming from adverts also enriched the language. Translations helped create the language of advertising as such, by developing its constituent parts: brands and slogans.
Keywords: translated adverts; adverts of the 1920s and 1930s; language of advertising; brand